The Relationship Of Mother's Knowledge And Attitude In Giving Stimulation Of Infant Growth And Development - Marniwati Lafau; Debi Novita Siregar; Lelli Kristia Wahyuningsih; Liana; Lidia Siregar; Kusniati Nova Nainggolan (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Child growth and development is the result of the interaction process of hereditary factors, hereditary constitution and environmental factors at the prenatal stage or at the postnatal stage. Growth and development occur simultaneously. This research aims to determine the relationship between knowledge and attitudes of mothers in providing stimulation for baby growth and development in the Viktory Clinic Work Area, South Nias in 2024. The type of research used is quantitative with a cross sectional approach. The sample in this study was all mothers who had babies aged 0-12 months in the Viktory Clinic Working Area, South Nias, totaling 40 people. with total sampling technique. Data analysis was carried out univariate and bivariate using the chi square test.  The research results showed that of the 40 respondents, the majority did not stimulate baby growth and development, 28 respondents (70%). Most mothers' knowledge about stimulating baby growth and development was sufficient, 18 respondents (45%) and a good minority, 8 respondents (20%). The majority of mothers' attitudes regarding stimulating baby's growth and development were negative, as many as 29 respondents (72.5%). There is a relationship between maternal knowledge and stimulation of baby growth and development with a p-value of 0.000 (p<0.05). There is a relationship between maternal knowledge and stimulation of baby growth and development with a p-value of 0.001 (p<0.05). The conclusion of this research is that there is a relationship between knowledge and attitudes of mothers in providing stimulation for baby growth and development.